The basis of report-difference superiority in delayed perceptual comparison tasks. - Pilling, Michael; Barrett, Douglas J.K.; Gellatly, Angus (Memory & Cognition, 2020)
A major role for visual short-term memory (VSTM) is to mediate perceptual comparisons of visual information across successive glances and brief temporal interruptions. Research that has focused on the comparison process has noted a marked tendency for performance to be better when participants are required to report a difference between the displays rather than report the absence of a difference (i.e. a sameness). We refer to this performance asymmetry as report-difference superiority (RDS). It has been suggested that RDS reflects the operation of a reflexive mechanism that generates a mismatch signal during the comparison of visual input with information maintained in VSTM. This bottom-up mechanism therefore gives evidence for the presence of a feature change but not for the absence of such a change; consequently, a sameness is harder to detect than a difference between two displays. We test this explanation, and determine whether by itself it is a sufficient explanation of the RDS. In a delayed comparison task we find the RDS effect is most prevalent when items retain the same display locations; however, the effect does persist even when compared item locations were scrambled across memory and test arrays. However, with a conjunction task this scrambling of locations was effective in wholly abolishing the RDS effect. We consider that the RDS effect is a consequence of local comparisons of features, as well as global statistical comparisons.